Editorial: Towards Inclusive Education - Tamara Cierpiałowska; Irmina Rostek (Horyzonty Wychowania)
We present you a new issue of Horizons of Education dedicated to the idea of inclusive education. Since the modern school is made up of students with diverse abilities and needs, thus, the heterogeneous class teams pose a challenge for educators, conducting discussions around this topic that seems nowadays to be extremely important. As Zenon Gajdzica and Edyta Widawska point out in the article, included in this issue, that, although inclusive education is declaratively a priority for educational policies, in practice, its complexity, fears or even resistance of school environments, not always the sufficient institution and /or teacher preparation, as well as other factors of various nature, constitute significant obstacles to for its implementation.